2001
DOI: 10.5172/conu.10.3-4.163
|View full text |Cite
|
Sign up to set email alerts
|

Vision screening of school children: Should it be continued?

Abstract: Vision screening of all children at school entry has been a traditional practice for many years. Recently, decisions have been made to discontinue screening and to rely on parent and teacher referral methods instead. A review of the literature suggested that parent and teacher referral methods of screening were less than satisfactory, and that professional screening of all children at school entry age should be continued.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…The systematic review supported screening by school nurses with appropriate professional support and training by orthoptists [64]. It was found that nurses were highly accurate in screening for visual acuity, but may benefit from more assistance and training in detecting strabismus.…”
Section: School Age (6+ Years)mentioning
confidence: 95%
See 2 more Smart Citations
“…The systematic review supported screening by school nurses with appropriate professional support and training by orthoptists [64]. It was found that nurses were highly accurate in screening for visual acuity, but may benefit from more assistance and training in detecting strabismus.…”
Section: School Age (6+ Years)mentioning
confidence: 95%
“…The first review, of medium quality, supported screening of children aged six years and over by school nurses with appropriate professional support and training by orthoptists. [64] The second review, of high quality, concluded that orthoptic screening programs performed better than health visitor or general practitioner screening programs in terms of yield and positive predictive value when screening children aged three to six years. [65] One randomised controlled trial of medium quality evaluated the screening of three to six year old children.…”
Section: Overall Summary -Screener Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…One systematic review reported that nurses were highly accurate in screening for visual acuity, but may benefit from more assistance and training (Pattison & Plymat 2001).…”
Section: School Age (6+ Years)mentioning
confidence: 99%
“…Earlier vision screening can detect children with amblyopia and amblyogenic factors at an appropriate age where treatment is effective. 1,[6][7][8][9][10][11][12] The American Academy of Pediatrics recommends formal preschool vision screening, including formal testing of visual acuity and ocular alignment, beginning at age 3. 7 However, despite these recommendations, most children are not screened, perhaps because traditional vision screening methods typically are felt to have high overreferral rates, low sensitivity, and low specificity.…”
mentioning
confidence: 99%